The Symbiosis-Related ERN Transcription Factors Act in Concert to Coordinate Rhizobial Host Root Infection(1) - Cerri, Marion R. (Plant Physiol, 2016)
Legumes improve their mineral nutrition through nitrogen-fixing root nodule symbioses with soil rhizobia. Rhizobial infection of legumes is regulated by a number of transcription factors, including ERF Required for Nodulation1 (ERN1). Medicago truncatula plants defective in ERN1 are unable to nodulate, but still exhibit early symbiotic responses including rhizobial infection. ERN1 has a close homolog, ERN2, which shows partially overlapping expression patterns. Here we show that ern2 mutants exhibit a later nodulation phenotype than ern1, being able to form nodules but with signs of premature senescence. Molecular characterization of the ern2-1 mutation reveals a key role for a conserved threonine for both DNA binding and transcriptional activity. In contrast to either single mutant, the double ern1-1 ern2-1 line is completely unable to initiate infection or nodule development. The strong ern1-1 ern2-1 phenotype demonstrates functional redundancy between these two transcriptional regulators and reveals the essential role of ERN1/ERN2 to coordinately induce rhizobial infection and nodule organogenesis. While ERN1/ERN2 act in concert in the root epidermis, only ERN1 can efficiently allow the development of mature nodules in the cortex, probably through an independent pathway. Together, these findings reveal the key roles that ERN1/ERN2 play at the very earliest stages of root nodule development.